Comprehensive New Insights and Perspectives into Ti‐Based Anodes for Next‐Generation Alkaline Metal (Na+, K+) Ion Batteries. Issue 27 (13th August 2018) - Wang, Nana; Chu, Chenxiao; Xu, Xun; Du, Yi; Yang, Jian; Bai, Zhongchao; Dou, Shixue
Abstract: Sodium ion batteries (NIBs) and potassium ion batteries (KIBs) are promising candidates for large‐scale energy storage systems, with a similar "rocking chair" working principle to lithium ion batteries due to their earth abundance and lower cost. One of the major challenges in NIB research is the search for suitable anode materials with long lifetimes and high specific capacities. The research on KIBs is still in its infancy. Titanium‐based anodes present low lattice strain, high safety, and overall stability during cycling, which make them promising for large‐scale systems, especially for stationary batteries. In this review, the latest progress on titanium‐based anodes for NIBs and KIBs is summarized, including titanium dioxide and its composite, Na x TiO2 systems, NaTi2 (PO4 )3, titanates, and MXenes. The synthesis methods, modification methods, and sodium or potassium ion storage mechanisms of titanium‐based anodes are detailed; also the current challenges and future opportunities are discussed. Abstract : The recent progress in titanium‐based anodes employed in sodium and potassium ion batteries is herein summarized . Ti‐based anodes exhibit the advantages of high safety, low cost, and high stability, which is important for large‐scale energy storage systems. A detailed and in‐depth understanding of metal ion storage mechanisms, and structure‐modification–property relationships of titanium based electrodes are provided in this review.